Association Between Homocysteine and Vascular Calcification Incidence, Prevalence, and Progression in the MESA Cohort. Issue 3 (4th February 2020) - Karger, Amy B.; Steffen, Brian T.; Nomura, Sarah O.; Guan, Weihua; Garg, Parveen K.; Szklo, Moyses; Budoff, Matthew J.; Tsai, Michael Y.
Abstract : Background: While elevated homocysteine has been associated with calcification in several studies, its importance as a cardiovascular risk factor remains unclear. This study examines the relationship between homocysteine and vascular and valve calcification in the MESA (Multi‐ethnic Study of Atherosclerosis) cohort. Methods and Results: MESA participants with baseline homocysteine measurements and cardiac computed tomography scans were included (N=6789). Baseline and follow‐up assessment of vascular (coronary artery [CAC], descending thoracic aorta [DTAC]) and valve (aortic valve [AVC], mitral annular [MAC]) calcification was performed. Prevalence ratio/relative risk regression was used to assess the relationship of homocysteine with prevalent and incident calcification, and multivariable logistic regression was used to assess associations between homocysteine and calcification progression. Elevated homocysteine was associated with greater relative risk of prevalent and incident CAC and incident DTAC. We also identified a strong association between elevated homocysteine and CAC and DTAC progression. Elevated homocysteine was found to confer a >2‐fold increased risk of severe CAC progression (defined as ΔCAC ≥100/year) and an ≈1.5‐fold increased risk for severe DTAC progression (defined as ΔDTAC ≥100/year). Conclusions: To our knowledge, this is the first study demonstrating an association between elevated homocysteine and both incidence and progression of coronary and extra‐coronary vascular calcification. Our findings suggest a potential role for elevated homocysteine as a risk factor for severe vascular calcification progression. Future studies are warranted to further assess the utility of homocysteine as a biomarker for vascular calcification incidence and progression. Clinical Trial Registration: https://www.clinicaltrials.gov/ . Unique identifier: NCT00005487.